Trend Analysis: Consumer Behavior towards the Decision to Use Shopee Paylater - Serenade, Vincensia; Gusniar, Bella; Rahmasari, Yunita (UPI YPTK Journal of Business and Economics, 2024)
Financial Technology (Fintech) has significantly transformed the financial landscape by integrating traditional financial systems with modern technology. This study examines consumer behavior towards Shopee PayLater, a prominent "Buy Now, Pay Later" (BNPL) service in Indonesia. While PayLater services offer numerous benefits, they also pose risks, particularly encouraging overspending beyond financial capabilities. The research aims to understand the impact of consumer behavior on the decision to use Shopee PayLater. A questionnaire survey conducted among 116 respondents in Sukoharjo Regency, Central Java, utilized multiple linear regression analysis via SPSS software. Results indicate that consumer behavior significantly and positively influences the decision to adopt Shopee PayLater, with financial constraints being a major factor driving its use. Validity and reliability tests confirmed the robustness of the measurement instruments, and normality tests ensured appropriate data distribution for analysis. The coefficient of determination revealed that consumer behavior explains 35.8% of the variance in the decision to use Shopee PayLater. The findings underscore the importance of enhancing service quality, incorporating risk perception, promoting financial literacy, and developing regulatory policies to ensure the sustainable growth of BNPL services. This study provides valuable insights for Shopee, the fintech industry, and policymakers in Indonesia, highlighting the need for strategic initiatives to optimize BNPL offerings and promote financial inclusion and economic empowerment.